Helium ion microscopy of enamel crystallites and extracellular tooth enamel matrix - Bidlack, Felicitas B.; Huynh, Chuong; Marshman, Jeffrey; Goetze, Bernhard (Frontiers in Physiology, 2014)
An unresolved problem in tooth enamel studies has been to analyze simultaneously and with sufficient spatial resolution both mineral and organic phases in their three dimensional (3D) organization in a given specimen. This study aims to address this need using high-resolution imaging to analyze the 3D structural organization of the enamel matrix, especially amelogenin, in relation to forming enamel crystals. Chemically fixed hemi-mandibles from wild type mice were embedded in LR White acrylic resin, polished and briefly etched to expose the organic matrix in developing tooth enamel. Full-length amelogenin was labeled with specific antibodies and 10 nm immuno-gold. This allowed us to use and compare two different high-resolution imaging techniques for the analysis of uncoated samples. Helium ion microscopy (HIM) was applied to study the spatial organization of organic and mineral structures, while field emission scanning electron microscopy (FE-SEM) in various modes, including backscattered electron detection, allowed us to discern the gold-labeled proteins. Wild type enamel in late secretory to early maturation stage reveals adjacent to ameloblasts a lengthwise parallel alignment of the enamel matrix proteins, including full-length amelogenin proteins, which then transitions into a more heterogeneous appearance with increasing distance from the mineralization front. The matrix adjacent to crystal bundles forms a smooth and lacey sheath, whereas between enamel prisms it is organized into spherical components that are interspersed with rod-shaped protein. These findings highlight first, that the heterogeneous organization of the enamel matrix can be visualized in mineralized en bloc samples. Second, our results illustrate that the combination of these techniques is a powerful approach to elucidate the 3D structural organization of organic matrix molecules in mineralizing tissue in nanometer resolution.